Avances en el trastorno por deficit de atención e hiperactividad. ¿Qué nos aporta la neuroimagen? - Quintero, J.; Navas, M.; Fernández, A.; Ortiz, T. (Actas Espanolas de Psiquiatria, 2009)
In attention deficit hyperactivity disorder (ADHD) is a multifactorial and clinically heterogeneous disorder that is the result of the combination of environmental, genetic and biological factors. Its high prevalence, added to the high level of maladaptation occurring in the children affected and the elevated comorbidity with other psychiatric disorders have lead to new scientific interest in this disorder. Especially in recent years, there has been a considerable increase in its study using neuroimaging techniques. Structural and functional imaging studies suggest that the ADHD pathophysiology would be conditioned by a dysfunction in the fronto-subcortical pathways, as well as imbalances in the dopaminergic and noradrenergic systems.